Dietary change influences the composition of the fecal microbiota in two rescued wild raccoon dogs (Nyctereutes procyonoides) - Li, Hailong; Bao, Lei; Wang, Tianming; Guan, Yu (Frontiers in Microbiology, 2024)
The gut microbiota of wild animals, influenced by various factors including diet, nutrition, gender, and age, plays a critical role in their health and disease status. This paper focuses on the raccoon dog (Nyctereutes procyonoides), a commonly found wild animal, and its gut microbiota composition in response to dietary shifts. The study aimed to compare the fecal bacterial communities and diversity of rescued raccoon dogs fed three different diet types (fish and amphibians, mixed protein with maize, and solely maize) using high-throughput sequencing. Results indicated that the dietary composition significantly influenced the gut microbiota, with notable differences in the abundance of several key phyla and genera. The study identified Firmicutes as the dominant phylum in all diet groups, with notable variations in the relative abundances of Bacteroidota, Proteobacteria, and Verrucomicrobiota. Notably, the group solely fed maize exhibited a significant increase in Proteobacteria, potentially linked to dietary fiber and lignin degradation. Genus-level analysis highlighted significant differences, with Lactobacillus and Bifidobacterium responding to dietary shifts. The genus Akkermansia in Verrucomicrobiota can be identified as a marker for assessing the health of the gut and deserves further investigation. Gender-specific differences in the gut microbiota were observed, highlighting the influence of individual variation. Furthermore, the analysis of bacterial functions suggested a connection between diet and host metabolism, emphasizing the need for further research to understand the complex mechanisms underlying the relationship between dietary composition and gut microbiota in wild animals. These findings provide crucial insights into the conservation and rescue efforts for wild animals.